(untitled) (Global Journal of Science Frontier Research, 2025)
The results of the experimental determination of the propagation speed of the Sun s radio emission are presented confirming the position of the general theory of relativity on the inconstancy of the speed of light in a vacuum as well as the position of the previously formulated hypothesis about the physical essence of time as the movement of the Universe in the direction of the orthogonal fourth spatial dimension due to its own expansion